1994
DOI: 10.1073/pnas.91.18.8423
|View full text |Cite
|
Sign up to set email alerts
|

Roles of heme iron-coordinating histidine residues of human hemopexin expressed in baculovirus-infected insect cells.

Abstract: Hemopexin (Hx), the major heme-binding plasma glycoprotein, scavenges circulating heme and performs an antioxidant function. In the present study, human Hx was expressed in a baculovirus system and its presumed essential His residues were mutated to Thr as a means of investigating their participation in heme binding. The recombinant Hx proteins were purified by sequential chromatography on Con A-agarose and SP-Sepharose. The purified recombinant wild-type Hx retained its heme binding. The binding constant for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 36 publications
2
37
0
Order By: Relevance
“…The oligosaccharides attached to this protein promote glycoprotein folding, contribute to proteinÁprotein interactions, regulate other ligand recognition processes, and stabilize the protein, making it resistant to proteolysis (Helenius and Aebi 2004;Ohtsubo and Marth 2006). Up to now, the role of the oligosaccharide in this glycoprotein has been unclear; however, Satoh et al (1994) reported that N-linked glycosylation is an essential part of the high affinity of human hemopexin for heme, and Hirayama et al (2004) reported that fish Wap65 binds heme.…”
Section: Discussionmentioning
confidence: 99%
“…The oligosaccharides attached to this protein promote glycoprotein folding, contribute to proteinÁprotein interactions, regulate other ligand recognition processes, and stabilize the protein, making it resistant to proteolysis (Helenius and Aebi 2004;Ohtsubo and Marth 2006). Up to now, the role of the oligosaccharide in this glycoprotein has been unclear; however, Satoh et al (1994) reported that N-linked glycosylation is an essential part of the high affinity of human hemopexin for heme, and Hirayama et al (2004) reported that fish Wap65 binds heme.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, RT-PCR and Western blot analyses confirmed the stable expression of human rHPX at both transcriptional and translational levels. Since human rHPX bears extensive human-specific glycosylation, mammalian expression systems, such as HEK293 or CHO cell lines, could be suitable hosts to provide sufficient post-translational modifications to afford heme binding and expected rHPX bioactivity (15). The CHO cell line is the premier expression host for therapeutic protein production due to its adaptability to various culture conditions, plasticity in terms of genetic alterations (18) and human-like glycosylation (24).…”
Section: Discussionmentioning
confidence: 99%
“…Their initial attempts to express human HPX in an E. coli system produced a non-glycosylated protein with no heme-binding ability (15). Protein expression in prokaryotic system is associated with challenges such as limited eukaryotic post-translational machinery function, protein aggregation, and generation of inclusion bodies (33).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations